Cover me ebook - Mann, Catherine (Elite Force: That Others May Live, 2011)
"Nobody writes to-die-for military heroes like Catherine Mann!" — Suzanne Brockmann, New York Times bestselling author of Tall, Dark and Devastating It should have been a simple mission... Pararescueman Wade Rocha fast ropes from the back of a helicopter into a blizzard to save a climber stranded on an Aleutian Island, but Sunny Foster insists she can take care of herself just fine... But when it comes to passion, nothing is ever simple... With the snowstorm kicking into overdrive, Sunny and Wade hunker down in a cave and barely resist the urge to keep each other warm... until they discover the frozen remains of a horrific crime... Unable to trust the local police force, Sunny and Wade investigate, while their irresistible passion for each other gets them more and more dangerously entangled... "When you read Catherine Mann you... get nonstop action, nail-biting suspense, and heart-stopping romance." —The Romance Studio